The Risk Factors and Clinical Features of Posttraumatic Seizure in Preschool-Aged Children - Taewoo Shin; Kitaek Oh; Byung Ho Cha (Korean Child Neurology Society, 2019)
Purpose This study aimed to identify the clinical characteristics and risk factors of post-traumatic seizure (PTS) in preschool-aged children. Methods This study is based on a retrospective electronic medical record review of 1,576 children under 6 years old, who visited our hospital by head trauma from January 1, 2011 to December 31, 2015. We reviewed demographics, causes of head trauma, radiologic findings, Glasgow Coma Scale (GCS) score, and characteristics of seizure. PTS was divided into 3 groups of immediate (within the day of head trauma), early (within 7days) and late (after 7days) seizures. Results Of the 1,576 head traumas, 3.4% developed PTS of which 32.1% occurred immediately, 11.3% early, 56.6% lately. The mean age was 2.02±1.63 years and 60.6% was male, 2.6% had fever at the time of visit, and 2.9% had a history of seizures. The causes of head injuries were blunt trauma (34.5%), fall down (29.5%), slip down injury (25.1%), passenger traffic accidents (7.2%), pedestrian traffic accident (1.9%), and causes unknown (1.8%). The severity of traumatic brain injury (TBI) was mild in 99.0%, moderate in 0.4%, and severe in 0.5%. On radiologic findings, 88.6% was normal, 6.0% had skull fracture, 2.8% had intracranial hemorrhage (ICH) and 2.7% had both skull fracture and ICH. Conclusion The incidence of PTS in preschool-aged children was 3.4%. The risk factors for PTS in preschool-aged children were fever over 38.0˚C, history of seizure, TBI severity by GCS score. Age, sex, causes of head trauma, and radiologic findings did not correlated to the occurrence of PTS.